Clone Configuration and Spatial Genetic Structure of Two Halophila ovalis Populations With Contrasting Internode Lengths - Xu, Na-Na; Jiang, Kai; Biswas, Shekhar R.; Tong, Xin; Wang, Rong; Chen, Xiao-Yong (Frontiers in Ecology and Evolution, 2019)
Fine-scale spatial genetic structure (SGS) is predominantly determined by gene flow. While sexually reproducing plants can disperse their genes through pollen and seed grains, clonal plants can additionally disperse genes through clonal growth. Plants’ clonal reproduction strategy, however, often varies within and between species. Still, the effect of differential clonal reproduction strategy on fine-scale SGS remains somewhat unclear. Halophila ovalis is a fast-growing clonal seagrass, whose internode length (which defines a species’ clonal reproduction strategy) varies among populations. Using eight polymorphic microsatellites, here we compare the genetic diversity, clonal structure and fine-scale SGS of two H. ovalis populations with contrasting internode lengths (Yingluo versus Xialongwei populations). We found moderate to high genotypic and allelic richness and heterozygosities in both populations. Compared to Xialongwei population, genetic and genotypic diversity was significantly lower in Yingluo population. Although their internode length was relatively short, clones of Yingluo population spread farther than those of Xialongwei population. Sexual-to-vegetative dispersal variance ratios were 34.6 and 445.5 in Yingluo and Xialongwei populations, respectively. In both populations, clonal growth significantly intensified the SGS, especially in short distance classes. The SGS at small distance classes were weaker in Yingluo than Xialongwei, in part, due to more intermingled distribution of genets and more extensive clonal expansion in the former population. Our results indicate that vegetative dispersal variance/distance, rather than internode length, plays a crucial role in shaping the fine-scale genetic structure.